2018
DOI: 10.1111/epi.13993
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of eslicarbazepine acetate versus controlled‐release carbamazepine monotherapy in newly diagnosed epilepsy: A phase III double‐blind, randomized, parallel‐group, multicenter study

Abstract: SummaryObjective: We assessed the efficacy and safety of once-daily eslicarbazepine acetate in comparison with twice-daily (BID) controlled-release carbamazepine (carbamazepine-CR) monotherapy in newly diagnosed focal epilepsy patients. Methods: This randomized, double-blind, noninferiority trial (NCT01162460) utilized a stepwise design with 3 dose levels. Patients who remained seizure-free for the 26-week evaluation period (level A: eslicarbazepine acetate 800 mg/carbamazepine-CR 200 mg BID) entered a 6-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 35 publications
3
76
0
4
Order By: Relevance
“…10,[12][13][14] These trials showed that levetiracetam, zonisamide, lacosamide, and eslicarbazepine were noninferior to carbamazepine-CR, and provided class I evidence of efficacy in adults with focal epilepsy that led to approval of these drugs as monotherapy options in Europe. 10,[12][13][14] These trials showed that levetiracetam, zonisamide, lacosamide, and eslicarbazepine were noninferior to carbamazepine-CR, and provided class I evidence of efficacy in adults with focal epilepsy that led to approval of these drugs as monotherapy options in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…10,[12][13][14] These trials showed that levetiracetam, zonisamide, lacosamide, and eslicarbazepine were noninferior to carbamazepine-CR, and provided class I evidence of efficacy in adults with focal epilepsy that led to approval of these drugs as monotherapy options in Europe. 10,[12][13][14] These trials showed that levetiracetam, zonisamide, lacosamide, and eslicarbazepine were noninferior to carbamazepine-CR, and provided class I evidence of efficacy in adults with focal epilepsy that led to approval of these drugs as monotherapy options in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Four trials [17][18][19][20] were included in the review, all of which were included in the meta-analysis ( Figure 1). Four trials [17][18][19][20] were included in the review, all of which were included in the meta-analysis ( Figure 1).…”
Section: Results Of the Searchmentioning
confidence: 99%
“…26,27 Notably, this endpoint is more specific and less influenced by the nocebo effect than the occurrence of adverse events. 20 The selective enhancement of slow rather than fast inactivation of voltage-gated sodium channels operated by LCS might have also contributed, but no definitive conclusions could be drawn. The older age of the population enrolled in the trial and the higher rate of patients over 65 years might partially explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…This may therefore reflect an improvement in overall tolerability as patients withdrew from AED polytherapy to monotherapy (since the majority of patients treated with ESL monotherapy at the last visit had previously received concomitant AED treatment[s] prior to withdrawing to ESL monotherapy). 2 Combining drugs that block voltage-dependent sodium channels is known to increase the likelihood of neurotoxic side effects (such as dizziness). These findings are consistent with those of a previous Euro-Esli subanalysis, which demonstrated that the incidence of AEs leading to discontinuation (as well as the overall incidence of AEs) was significantly lower in patients treated with less than two concomitant AEDs than in those treated with two or more concomitant AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…2 These findings are supported by the results of two phase III withdrawal to monotherapy trials, 3,4 which resulted in approval for ESL in the monotherapy setting in the United States. 2 These findings are supported by the results of two phase III withdrawal to monotherapy trials, 3,4 which resulted in approval for ESL in the monotherapy setting in the United States.…”
mentioning
confidence: 87%